Lactoperoxidase system in the dairy industry: Challenges and opportunities - Emmanuelle Silva; Juliana Oliveira; Yhelda Silva; Stela Urbano; Danielle Sales; Edgar Moraes; Adriano Rangel; Katya Anaya (Czech Journal of Food Sciences, 2020)
The objective of this review was to search the literature for studies on the lactoperoxidase system (LPS) as milk natural preservation, action mechanisms, usage methods and perspectives for the dairy industry. A comprehensive literature review approach was conducted for collecting evidence in scientific publications. The biological properties of milk promote the development of microorganisms which compromise its quality, therefore demanding the use of techniques for preserving the milk matrix from its collection until processing. Within this context, LPS could represent an alternative to guarantee the safety of this food in are as where refrigeration is not possible; in addition, studies on applying this system in the dairy industry have been explored, as is the case in the test for verifying pasteurisation efficiency according to determining the lactoperoxidase enzyme activity. Natural antimicrobial properties of LPS make it a promising alternative for the industrial preservation and processing of milk, especially when considering the current quality standard demanded by the market. However, the potential of LPS as a biopreservative is still little technically and scientifically explored, which implies the need to develop new studies.